Efecto del inhibidor de fosfodiesterasa tipo 4 —rolipram, sobre la maduración in vitro de oocitos bovinos - López, Yuddy S.; Mejía, Ana M.; Escobar, Elder E.; Agudelo Jaramillo, Bernardo; Vásquez, Neil A.; Echavarría, Hernán (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Gonadotropic follicle stimulating hormone (FSH) and lutenizing hormone (LH) induce intracellular cyclic AMP (cAMP) production during the in vitro maturation (IVM) of bovine oocytes. Cyclic AMP exerts a dual effect, where high intraoocyte cAMP levels are responsible for oocyte meiotic blockage, while high cAMP levels into the granulose cells induce oocyte maturation. Intracellular cAMP levels are regulated by phosphodiesterases (PDE)-mediated hydrolysis, enzymes having a specific follicle expression pattern. Oocyte expresses typo 3 PDE (PDE 3), while granulose cells expresses type 4 PDE (PDE 4). With the aim to test the effect of the specific PDE 4 inhibitor rolliprom on percentage in vitro nuclear maturation (IVNM) of bovine oocytes, 629 cumulus-oocyte complexes (COC) were cultured at 38.5 ºC/CO2 5%/24 h on TCM-199 medium with pFSH and hrLH with or without rolipram. Experimental groups were: gonadotrophins alone, gonadotropins + rolipram (25, 50, or 75 µM), rolipram 50 µM + gonadotrophins, and control (media without stimulus). In order to determinate the nuclear maturation percentage by the first polar body expulsion, oocytes were dyed with DAPI and evaluated by fluorescence. Rolipram 50 µM stimulated bovine oocyte nuclear maturation in a similar way to gonadotrophins stimulus (76.83 vs. 79.46%, p > 0.05) did, but in a higher way than rolipram 25 µM (31.25%) or 75 M (28.61%). The COC cultured with rolipram 50 µM+gonadotrophins maturated in a lower proportion (63.74%) than did with gonadotropins (p < 0.01) or rolipram 50 µM (p < 0.05). A dose-dependent response of percentage of IVNM of bovine oocytes was detected. Thus rolipram 50 µM, exerts a similar effect of gonadotropins on oocyte maturation. In addition, the presence of gonadotropic stimulus and a PDE inhibitor may induce a desensitization response of the cAMP way, as suggested by the reduction of the percentage of maturation.